PYN-PHT-based high-temperature piezoelectric ceramic material and preparation method thereof

CN119430924APending Publication Date: 2025-02-14XIDIAN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411602707.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

[0004]国内外对高温压电陶瓷的研究大多集中在无铅体系上,然而无铅体系的压电性能较为薄弱,难以满足实际应用中对高效能量转换的要求,限制了其实际应用

Benefits of technology

[0037] A PYN-PHT-based high-temperature piezoelectric ceramic material of the present invention replaces the A-position element (Pb) in the perovskite structure by M', and M' replaces the B-position element (Ti, Hf, Yb in the perovskite structure by M', and M' replaces the B-position element (Ti, Hf, Yb in the perovskite structure by M'. One or more of , Nb) realizes double doping, improves the formulation, and improves the piezoelectric performance and temperature reliability of high-temperature piezoelectric ceramic materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430924A_ABST
    Figure CN119430924A_ABST
Patent Text Reader

Abstract

The invention relates to a PYN-PHT-based high-temperature piezoelectric ceramic material and a preparation method thereof, the chemical formula of the high-temperature piezoelectric ceramic material is 0.1 Pb (Yb0. 5Nb0. 5) O3-0.9 Pb (Hf1-yTiy) O3 + xmol% (M '+ M' '), M' represents an ion with the ion radius of # imgabs 0 #, M ''represents an ion with the ion radius of # imgabs 1 #, x is more than or equal to 0.1 and less than or equal to 2.0, and y is more than or equal to 0.5 and less than or equal to 0.65. According to the invention, M'is used for replacing an A-site element (Pb) in a perovskite structure, and M ''is used for replacing one or more of B-site elements (Ti, Hf, Yb and Nb) in the perovskite structure, so that double doping is realized, the formula is improved, and the piezoelectric property and temperature reliability of the high-temperature piezoelectric ceramic material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of piezoelectric ceramic materials, and in particular relates to a PYN-PHT-based high-temperature piezoelectric ceramic material and a preparation method thereof. Background Art

[0002] Piezoelectric materials are able to achieve conversion between electrical and mechanical energy and are highly valuable in various electronic devices such as actuators and sensors. In recent years, there has been an increasing demand for high-performance piezoelectric materials that can operate effectively over a wide temperature range, especially in important fields such as new energy, aerospace, and oil exploration. In high-temperature piezoelectric sensing applications, the key performance indicators of piezoelectric materials are the piezoelectric coefficient and the operating temperature range. Although significant progress has been made in the development of high-temperature devices, the pursuit of materials that provide both thermal stability and significant piezoelectric performance remains a daunting challenge.

[0003] During use, piezoelectric devices are usually not equipped with dedicated cooling equipment, so the temperature rise of the device is very obvious. In high temperature environment, the performance of the device usually undergoes thermal depolarization. Perovskite structured ferroelectric materials have played a key role in many piezoelectric devices due to their excellent piezoelectric coefficient and dielectric constant. PYN-PHT perovskite ceramics are composed of Pb(Yb 0.5 Nb 0.5 )O3 and Pb(Hf 1-y Ti y )O3, with the advantages of high piezoelectric coefficient and high Curie temperature, it can still maintain good performance stability in high temperature environment, and is an ideal candidate material for high temperature piezoelectric applications. The excellent properties of PYN-PHT perovskite ceramics provide new ideas for the design of high temperature piezoelectric devices and promote the application and development of high temperature piezoelectric ceramics.

[0004] Most of the research on high-temperature piezoelectric ceramics at home and abroad is focused on lead-free systems. However, the piezoelectric performance of lead-free systems is relatively weak, which makes it difficult to meet the requirements for efficient energy conversion in practical applications, limiting their practical applications. In the prior art, the problem of low piezoelectric coefficients is solved by constructing phase boundaries, but polymorphic phase boundaries are obviously temperature-dependent, resulting in unstable performance of the device under high temperature conditions. Therefore, the development of piezoelectric ceramic materials with both good piezoelectric performance and temperature reliability is still an urgent problem to be solved. Summary of the invention

[0005] In order to solve the above problems existing in the prior art, the present invention provides a PYN-PHT-based high-temperature piezoelectric ceramic material and a preparation method thereof. The technical problem to be solved by the present invention is achieved through the following technical solutions:

[0006] The first aspect of the present invention provides a PYN-PHT-based high temperature piezoelectric ceramic material, the chemical formula of which is 0.1Pb(Yb 0.5 Nb 0.5 )O3-0.9Pb(Hf 1-y Ti y )O3+xmol%(M'+M"), where M' represents the ionic radius. ions, M" represents the ionic radius ions, 0.1≤x≤2.0, 0.5≤y≤0.65.

[0007] In one achievable manner, the M' comprises: Li + , K + 、Na + , Ca 2+ or Sr 2+ ;

[0008] The "M" includes: Nb 5+ 、 5+ , Sb 5+ , W 6+ Or Mo 6+ .

[0009] In one achievable manner, the M' is Li + ;

[0010] The M” is Mo 6+ ;

[0011] 0.4≤x≤1.6;

[0012] y=0.55.

[0013] The second aspect of the present invention provides a method for preparing a PYN-PHT-based high temperature piezoelectric ceramic material, which is used to prepare the PYN-PHT-based high temperature piezoelectric ceramic material provided by the first aspect of the present invention, comprising the following steps:

[0014] S1: According to the chemical formula 0.1Pb(Yb 0.5 Nb 0.5 )O3-0.9Pb(Hf 1-y Ti y )O3+xmol%(M'+M"), weigh a Nb-containing compound and a Yb-containing compound, mix them, and then perform ball milling, drying and sintering in sequence to obtain a precursor powder;

[0015] S2: According to the chemical formula 0.1Pb(Yb 0.5 Nb 0.5 )O3-0.9Pb(Hf 1-y Tiy The precursor powder, the Pb-containing compound, the Ti-containing compound, the Hf-containing compound, the M'-containing compound, and the M"-containing compound are weighed and mixed to obtain a mixed powder; wherein M' represents an ionic radius of ions, M" represents the ionic radius ions, 0.1≤x≤2.0, 0.5≤y≤0.65;

[0016] S3: ball milling, drying, sieving, pre-calcining and grinding the mixed powder in sequence to obtain a primary pre-calcined powder;

[0017] S4: ball milling, drying, grinding and sieving the primary pre-burned powder in sequence to obtain a pre-synthesized powder;

[0018] S5: pressing the pre-synthesized powder into sheets to obtain a ceramic green body;

[0019] S6: The ceramic green body is sequentially subjected to vacuuming, isostatic pressing and sintering to obtain 0.1Pb(Yb 0.5 Nb 0.5 )O3-0.9Pb(Hf 1-y Ti y )O3+xmol%(M'+M")high temperature piezoelectric ceramic material.

[0020] In one achievable manner, the Nb-containing compound comprises Nb2O5;

[0021] The Yb-containing compound includes Yb2O3.

[0022] In one achievable manner, the Pb-containing compound includes Pb3O4;

[0023] The Ti-containing compound includes TiO2;

[0024] The Hf-containing compound includes HfO2;

[0025] The M'-containing compound includes Li2CO3;

[0026] The "M"-containing compound includes MoO3.

[0027] In one achievable manner, in step S1, ball milling includes:

[0028] Anhydrous ethanol was used as a grinding agent and zirconium oxide balls were used as ball milling media for ball milling, wherein the ball milling time was 10 to 12 hours and the ball milling speed was 300 r / min;

[0029] In the step S3 and the step S4, the ball milling includes:

[0030] Anhydrous ethanol is used as a grinding agent, and a mixture of zirconia balls of a first particle size and a second particle size is used as a ball milling medium to ball mill the powder to be ball milled, wherein the ball milling time is 18 to 24 hours, the ratio of the powder to be ball milled to the grinding agent is 1g:1.5 to 2.0ml, and the ratio of the ball milling medium to the powder to be ball milled is 2.3 to 3:1.

[0031] In one achievable manner, in step S1, the sintering temperature is 1050-1150° C., and the sintering time is 6 hours.

[0032] In one achievable manner, in step S3, pre-burning includes:

[0033] Put the powder to be pre-fired into a crucible and cover it, heat it to 600°C at a rate of 3°C / min, keep it warm for 60 minutes, then heat it to 850-950°C at a rate of 2.5°C / min, and keep it warm for 2-3 hours.

[0034] In one achievable manner, in step S6, sintering includes:

[0035] In an atmospheric atmosphere, the temperature is raised to 800-900°C at a rate of 2.5°C / min, kept at this temperature for 30 minutes, and then raised to 1150-1250°C at a rate of 3°C / min, and fired at a constant temperature for 2-3 hours.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] A PYN-PHT-based high-temperature piezoelectric ceramic material of the present invention realizes dual doping by replacing the A-site element (Pb) in the perovskite structure with M' and replacing one or more of the B-site elements (Ti, Hf, Yb, Nb) in the perovskite structure with M", thereby improving the formula and enhancing the piezoelectric performance and temperature reliability of the high-temperature piezoelectric ceramic material. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 It is a flowchart of the steps of a method for preparing a PYN-PHT-based high-temperature piezoelectric ceramic material provided by an embodiment of the present invention;

[0039] Figure 2 This is a piezoelectric performance data diagram of a PYN-PHT-based high-temperature piezoelectric ceramic material provided by an embodiment of the present invention;

[0040] Figure 3 This is a graph showing the change in dielectric constant of a PYN-PHT-based high-temperature piezoelectric ceramic material with temperature provided by an embodiment of the present invention;

[0041] Figure 4 This is a temperature dependence diagram of the d33 value of a PYN-PHT-based high-temperature piezoelectric ceramic material provided by an embodiment of the present invention. DETAILED DESCRIPTION

[0042] The present invention is further described in detail below with reference to specific embodiments, but the embodiments of the present invention are not limited thereto.

[0043] Embodiment 1

[0044] This embodiment provides a PYN-PHT-based high temperature piezoelectric ceramic material. The chemical formula of the high temperature piezoelectric ceramic material is 0.1Pb(Yb 0.5 Nb 0.5 )O3-0.9Pb(Hf 1-y Ti y )O3+xmol%(M'+M"), where M' represents the ionic radius. ions, M" represents the ionic radius ions, 0.1≤x≤2.0, 0.5≤y≤0.65.

[0045] Specifically, the 0.1Pb(Yb 0.5 Nb 0.5 )O3-0.9Pb(Hf 1-y Ti y )O3+xmol%(M'+M") high temperature piezoelectric ceramic material is a typical ternary composite perovskite structure, wherein Pb is the A-site element in the perovskite structure, Ti, Hf, Yb, and Nb are the B-site elements in the perovskite structure, and M' has an ionic radius similar to that of Pb, and M" has an ionic radius similar to that of the B-site element. Therefore, according to the principle of similarity of valence state and ionic radius, M' replaces the A-site element (Pb) in the perovskite structure, and M" replaces one or more of the B-site elements (Ti, Hf, Yb, and Nb) in the perovskite structure. M' replacing Pb will cause oxygen vacancies. The generation of oxygen vacancies will cause the unit cell to deform (contract and twist), and M' is easy to form dipoles with oxygen vacancies. The dipoles can rearrange their orientation under an external electric field, which plays a role in stabilizing the domain structure, thereby improving the temperature stability of the material. When M" enters the PYN-PHT solid solution, it will replace the B-site element according to the principle of similar ion radius. Since the valence state of the B-site element is high, in order to maintain the valence balance, vacancies will be generated at the A site to compensate for the excess charge, which is conducive to the movement of electric domains and domain walls, and the number of domains oriented along the electric field direction is increased, thereby greatly increasing the piezoelectric effect of the material. In this embodiment, M' replaces the A-site element (Pb) in the perovskite structure, and M" replaces the B-site element in the perovskite structure, thereby achieving dual doping, improving the formula, and improving the piezoelectric properties and temperature reliability of high-temperature piezoelectric ceramic materials.

[0046] In this embodiment, M' includes: Li + , K + 、Na + , Ca 2+ or Sr 2+ . M" includes: Nb 5+ 、 5+ , Sb 5+ , W 6+ Or Mo 6+ .

[0047] Specifically, Li + The ionic radius is K + The ionic radius is Na + The ionic radius is Ca 2+ The ionic radius is Sr 2+ The ionic radius is Pb 2+ The ionic radius is Therefore, Li + , K + 、Na + , Ca 2+ , Sr 2+ With and Pb 2+ Similar ionic radius and electronegativity, therefore, Li + , K + 、Na + , Ca 2+ , Sr 2+ Can dissolve into the lattice to replace Pb 2+ , generating oxygen vacancies. Nb 5+ The ionic radius is Ta 5+ The ionic radius is Sb 5+ The ionic radius is W 6+ The ionic radius is Mo 6+ The ionic radius is Among the B-site elements, Nb 5+ The ionic radius is Ti 4+ The ionic radius is Hf 4+ The ionic radius is Yb 3+ The ionic radius is Therefore, Nb 5+ 、 5+, Sb 5+ , W 6+ Or Mo 6+ When it enters the PYN-PHT solid solution, it will replace Nb according to the principle of ionic radius similarity. 5+ 、Ti 4+ , Hf 4+ , Yb 3+ One or more of these, and, due to Nb 5+ 、 5+ , Sb 5+ , W 6+ 、Mo 6 + The valence state of Nb is higher than or equal to that of B-site elements. 5+ 、 5+ , Sb 5+ , W 6+ Or Mo 6+ After entering the B position, the difference in electric charges inside the structure becomes larger. In order to maintain the balance of electric charges, vacancies will be generated at the A position to compensate for the excess charge. It should be understood that when M" is Nb 5+ When Nb 5+ content, improve the composition, when the structure of Nb 5+ When the content of increases, the difference in electricity prices within the structure can also become larger.

[0048] In one achievable manner, M' is Li + , M” is Mo 6+ , 0.4≤x≤1.6, y=0.55.

[0049] Specifically, the preparation method of the PYN-PHT-based high temperature piezoelectric ceramic material of this embodiment is described, see Figure 1 , Figure 1 It is a flow chart of the steps of a method for preparing a PYN-PHT-based high-temperature piezoelectric ceramic material provided by an embodiment of the present invention.

[0050] The present embodiment provides a method for preparing a PYN-PHT-based high-temperature piezoelectric ceramic material, comprising the following steps:

[0051] S1: According to the chemical formula 0.1Pb(Yb 0.5 Nb 0.5 )O3-0.9Pb(Hf 1-y Ti y )O3+xmol%(M'+M") The ratio of Nb to Yb in the mixture is: Nb-containing compound and Yb-containing compound are weighed, mixed, and then ball-milled, dried, and sintered in sequence to obtain a precursor powder.

[0052] In this embodiment, the Nb-containing compound includes Nb2O5, and the Yb-containing compound includes Yb2O3.

[0053] Specifically, step S1 includes:

[0054] S101: Weigh Nb2O5 and Yb2O3 in a molar ratio of 1:1 to form a precursor mixed powder. In this embodiment, the purity of Nb2O5 and Yb2O3 is 99.99%.

[0055] S102: placing the precursor mixed powder in a 50 ml ball milling bottle, using anhydrous ethanol as a grinding agent and zirconium oxide balls as a ball milling medium for ball milling, wherein the ball milling time is 10 to 12 hours and the ball milling speed is 300 r / min. In this embodiment, the anhydrous ethanol completely submerges the precursor mixed powder.

[0056] S103: The ball milled slurry obtained in S102 is placed in a blast drying oven for drying at a temperature of 60 to 80° C. for a drying time of 2 to 4 hours.

[0057] S104: The powder obtained by drying S103 is kept at 1050-1150° C. for 6 hours to obtain YbNbO4 precursor powder, wherein the heating rate is 5° C. / min.

[0058] S2: According to the chemical formula 0.1Pb(Yb 0.5 Nb 0.5 )O3-0.9Pb(Hf 1-y Ti y )O3+xmol%(M'+M") The ratio of Nb, Pb, Ti, Hf, M', and M" in the precursor powder, the Pb-containing compound, the Ti-containing compound, the Hf-containing compound, the M'-containing compound, and the M"-containing compound are weighed and mixed to obtain a mixed powder. Among them, M' represents an ionic radius of ions, M" represents the ionic radius ions, 0.1≤x≤2.0, 0.5≤y≤0.65.

[0059] In this embodiment, the Pb-containing compound includes Pb3O4, the Ti-containing compound includes TiO2, and the Hf-containing compound includes HfO2. During the weighing process, Pb3O4 and HfO2 are over-weighed by 3% and 1% respectively to compensate for their volatilization losses.

[0060] In one achievable manner, the compound containing M' includes Li2CO3, and the compound containing M" includes MoO3. That is, M' is Li + , M” is Mo 6+ .

[0061] S3: The mixed powder is ball-milled, dried, sieved, pre-calcined and ground in sequence to obtain a primary pre-calcined powder.

[0062] Specifically, step S3 includes:

[0063] S301: using anhydrous ethanol as a grinding agent, and using a mixture of zirconium oxide balls of the first particle size and the second particle size as a ball milling medium, the powder to be ball milled is ball milled, wherein the ball milling time is 18 to 24 hours, the ratio of the powder to be ball milled to the grinding agent is 1g:1.5 to 2.0ml, and the ratio of the ball milling medium to the powder to be ball milled is 2.3 to 3:1. In this embodiment, the first particle size is 5mm and the second particle size is 3mm. It should be understood that in this step, the powder to be ball milled is the mixed powder obtained in step S2.

[0064] S302: placing the ball-milled slurry obtained in S301 in a glass dish for drying at a temperature between 60 and 80° C. for 2 to 3 hours.

[0065] S303: Use an 80-mesh screen to sieve the powder obtained after drying in S301 to obtain a mixed pre-burned dry powder.

[0066] S304: Put the powder to be pre-fired into a crucible and cover it, heat it to 600℃ at a rate of 3℃ / min, keep it warm for 60min, then heat it to 850-950℃ at a rate of 2.5℃ / min, and keep it warm for 2-3h. In this step, pre-fire is carried out in an atmospheric atmosphere. During the pre-fire, the crucible is a closed environment. After the pre-fire is completed, it is naturally cooled to room temperature. It should be understood that the powder to be pre-fired in this step is the mixed pre-fired dry powder obtained in step S303.

[0067] S305: Put the powder cooled to room temperature after the pre-sintering in step S304 into an agate mortar and grind it into fine powder to obtain the first pre-sintering powder. Furthermore, the first pre-sintering powder is put into a packaging bag for standby use.

[0068] S4: The primary pre-burned powder is subjected to ball milling, drying, grinding and sieving in sequence to obtain a pre-synthesized powder.

[0069] Specifically, step S4 includes:

[0070] S401: using anhydrous ethanol as a grinding agent, and using a mixture of zirconium oxide balls of the first particle size and the second particle size as a ball milling medium, the first pre-sintered powder is ball milled, wherein the ball milling time is 18 to 24 hours, the ratio of the powder to be ball milled to the grinding agent is 1g:1.5 to 2.0ml, and the ratio of the ball milling medium to the powder to be ball milled is 2.3 to 3:1. In this embodiment, the first particle size is 5mm and the second particle size is 3mm. It should be understood that in this step, the powder to be ball milled is the first pre-sintered powder obtained in step S3.

[0071] S402: placing the ball-milled slurry obtained in S401 in a glass dish for drying at a temperature between 60 and 80° C. for 2 to 3 hours.

[0072] S403: Put the powder dried in step S402 into an agate mortar and grind it into fine powder.

[0073] S404: The fine powder ground in S403 is sieved using an 80-mesh sieve to obtain a pre-synthesized powder.

[0074] S5: Pressing the pre-synthesized powder into sheets to obtain ceramic green bodies.

[0075] Specifically, 0.75 to 1 g of pre-synthesized powder was weighed using weighing paper and placed in a mold. The mold containing the pre-synthesized powder was then moved to a tablet press for a press treatment at 3 MPa. After the press treatment, a disc-shaped ceramic green body with a cross-sectional diameter of 1 cm and a thickness of 1.2 mm was formed.

[0076] S6: The ceramic green body is vacuumized, isostatically pressed, and sintered in sequence to obtain 0.1Pb(Yb 0.5 Nb 0.5 )O3-0.9Pb(Hf 1-y Ti y )O3+xmol%(M'+M")high temperature piezoelectric ceramic material.

[0077] Specifically, step S6 includes:

[0078] S601: The ceramic green body obtained in step S5 is placed in a packaging bag and vacuumed to a degree of vacuum of 0.09 MPa.

[0079] S602: The vacuumed ceramic green body is placed in an isostatic pressing device and subjected to a densification treatment at 30 MPa for 20 minutes.

[0080] S603: sintering the pre-synthesized powder obtained in step S4 at 1200° C. for 2 to 3 hours to obtain cooked powder.

[0081] S604: The densified ceramic green body is embedded in the cooked powder obtained in step S603, placed in a box-type muffle furnace, heated to 800-900°C at a rate of 2.5°C / min in an atmospheric atmosphere, kept warm for 30 minutes, then heated to 1150-1250°C at a rate of 3°C / min, and fired at a constant temperature for 2-3 hours to obtain 0.1Pb(Yb 0.5 Nb 0.5 )O3-0.9Pb(Hf 1-y Ti y )O3+xmol%(M'+M")high temperature piezoelectric ceramic material.

[0082] The present embodiment provides a PYN-PHT-based high-temperature piezoelectric ceramic material and a preparation method thereof. By replacing the A-site element (Pb) in the perovskite structure with M' and replacing the B-site element in the perovskite structure with M", dual doping is achieved, the formula is improved, and the piezoelectric properties and temperature reliability of the high-temperature piezoelectric ceramic material are improved. The high-temperature piezoelectric ceramic material provided in the present embodiment can be prepared by a two-step solid-phase sintering method, and the preparation method is simple and has good repeatability. The PYN-PHT-based high-temperature piezoelectric ceramic material provided in the present embodiment achieves a higher piezoelectric constant d33, and the piezoelectric performance is stable in a higher temperature range, and can be widely used in aerospace, geological exploration and other fields.

[0083] Embodiment 2

[0084] Based on the first embodiment, this embodiment provides a PYN-PHT-based high temperature piezoelectric ceramic material, the chemical formula of which is 0.1Pb(Yb 0.5 Nb 0.5 )O3-0.9Pb(Hf 0.5 Ti 0.5 )O3+xmol%(Li + +Mo 6+ ), and changing the value of x to 0.4, 0.8, 1.2, 1.6 and 2.0, we get: 0.1Pb(Yb 0.5 Nb 0.5 )O3-0.9Pb(Hf 0.45 Ti 0.55 )O3+0.4mol%(Li + +Mo 6+ ) 、0.1Pb(Yb 0.5 Nb 0.5 )O3-0.9Pb(Hf 0.45 Ti 0.55 )O3+0.8mol%(Li + +Mo 6+ ) 、0.1Pb(Yb 0.5 Nb 0.5 )O3-0.9Pb(Hf 0.45 Ti 0.55 )O3+1.2mol%(Li + +Mo 6+ ) 、0.1Pb(Yb 0.5 Nb 0.5 )O3-0.9Pb(Hf 0.45 Ti 0.55 )O3+1.6mol%(Li + +Mo 6+ ) 、0.1Pb(Yb 0.5 Nb0.5 )O3-0.9Pb(Hf 0.45 Ti 0.55 )O3+2.0mol%(Li + +Mo 6+ ) five kinds of high temperature piezoelectric ceramic materials, and the performance of the high temperature piezoelectric ceramic materials after electrode plating was tested to further illustrate the PYN-PHT-based high temperature piezoelectric ceramic materials provided in this embodiment. Furthermore, due to Mo 6+ The ionic radius is According to the principle of ionic radius similarity, Mo 6+ Substitute Ti with the closest ionic radius among the B-site elements 4+ .

[0085] Specifically, 0.1Pb(Yb 0.5 Nb 0.5 )O3-0.9Pb(Hf 0.5 Ti 0.5 )O3+xmol%(Li + +Mo 6+ ) The high temperature piezoelectric ceramic material is thinned, polished, and silver-plated to plate electrodes on the surface of the high temperature piezoelectric ceramic material.

[0086] Furthermore, thinning includes:

[0087] 0.1Pb(Yb 0.5 Nb 0.5 )O3-0.9Pb(Hf 0.5 Ti 0.5 )O3+xmol%(Li + +Mo 6+ ) The high-temperature piezoelectric ceramic material is placed on a grinding machine, and sandpapers of 400 mesh, 800 mesh and 1200 mesh are used in sequence to thin the upper and lower surfaces until the thickness is reduced to 0.8 mm.

[0088] Polishing includes:

[0089] The thinned high-temperature piezoelectric ceramic material is placed on a polishing machine and polished using a suspension.

[0090] Silver plating includes:

[0091] The polished high-temperature piezoelectric ceramic material was suspended in a test tube with a capacity of 10 ml, anhydrous ethanol was added, and ultrasonic cleaning was performed in an ultrasonic cleaner for 15 minutes to remove impurities on the surface of the high-temperature piezoelectric ceramic material. Subsequently, the high-temperature piezoelectric ceramic material was placed on a heating table for drying at a drying temperature of 120°C. Silver electrodes with diameters of 1 mm and 0.8 mm were coated on the upper and lower surfaces of the dried high-temperature piezoelectric ceramic material using screen printing technology, and then immediately placed on a heating table for drying at 120°C for 30 minutes. After drying, the high-temperature piezoelectric ceramic material was placed in a muffle furnace, and a step temperature program was set to sinter the silver electrode. The sintering temperature was 600-650°C, and the temperature was kept at atmospheric atmosphere for 120 minutes.

[0092] Immerse the electrode-plated high-temperature piezoelectric ceramic material in 140°C silicone oil, apply a DC electric field of 2.3-3.5kV / mm, polarize the ceramic sheet for 15-20 minutes, take it out and cool it naturally to room temperature. Then use a quasi-static piezoelectric constant d33 tester to measure its d33 value at room temperature. The test results are as follows: Figure 2 As shown in the figure, the horizontal axis is the x value. When x=0, it is an undoped PYN-PHT-based ceramic, that is, 0.1Pb(Yb 0.5 Nb 0.5 )O3-0.9Pb(Hf 0.5 Ti 0.5 )O3, compared with the undoped PYN-PHT-based ceramics, Li + Substituting A-site elements (Pb), Mo in the perovskite structure 6+ Substituting the B-site elements (Ti 4+ ), significantly improving the piezoelectric coefficient of the material. When x is less than 0.8, as x increases, that is, as the content of doped ions in the PYN-PHT-based high-temperature piezoelectric ceramic material increases, d33 continues to increase, and when x = 0.8, d33 reaches a maximum value of 592pC / N.

[0093] Using high temperature dielectric instrument to measure 0.1Pb(Yb 0.5 Nb 0.5 )O3-0.9Pb(Hf 0.45 Ti 0.55 )O3+0.8mol%(Li + +Mo 6+ ) The dielectric constant of high temperature piezoelectric ceramic materials and the Curie temperature are obtained. The measurement results are as follows Figure 3 As shown, from Figure 3 It can be seen that at a frequency of 100Hz to 10kHz, 0.1Pb(Yb 0.5 Nb 0.5 )O3-0.9Pb(Hf 0.45 Ti 0.55)O3+0.8mol%(Li + +Mo 6 + )The Curie temperature of high-temperature piezoelectric ceramic materials is maintained in the high temperature range of about 340°C.

[0094] Using a quasi-static piezoelectric constant d33 tester, the 0.1Pb(Yb 0.5 Nb 0.5 )O3-0.9Pb(Hf 0.45 Ti 0.55 )O3+0.8mol%(Li + +Mo 6+ ) The d33 value of high temperature piezoelectric ceramic materials in the range of room temperature to 300℃, the measurement results are as follows Figure 4 As shown in the figure, PYN-PHT represents undoped PYN-PHT-based ceramics, PYN-PHT-0.8(Li + -Mo 6+ ) indicates the 0.1Pb(Yb 0.5 Nb 0.5 )O3-0.9Pb(Hf 0.45 Ti 0.55 )O3+0.8mol%(Li + +Mo 6+ ) high temperature piezoelectric ceramic materials. Figure 4 It can be seen that the 0.1Pb(Yb 0.5 Nb 0.5 )O3-0.9Pb(Hf 0.45 Ti 0.55 )O3+0.8mol%(Li + +Mo 6+ ) can significantly improve the d33 value and show excellent temperature stability.

[0095] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the protection scope of the present invention.

Claims

1. A PYN-PHT-based high temperature piezoelectric ceramic material, characterized in that: The chemical formula of the high temperature piezoelectric ceramic material is 0.1Pb(Yb 0.5 Nb 0.5 )O3-0.9Pb(Hf 1-y Ti y )O3+xmol%(M'+M"), where M' represents the ionic radius. ions, M" represents the ionic radius ions, 0.1≤x≤2.0, 0.5≤y≤0.

65.

2. A PYN-PHT-based high temperature piezoelectric ceramic material according to claim 1, characterized in that: The M' includes: Li + , K + 、Na + , Ca 2+ or Sr 2+ ; The "M" includes: Nb 5+ 、 5+ , Sb 5+ , W 6+ Or Mo 6+ .

3. A PYN-PHT-based high temperature piezoelectric ceramic material according to claim 1, characterized in that: The M' is Li + ; It is stated that M” is Mo 6+ ; 0.4≤x≤1.6; y=0.55。 4. A method for preparing a PYN-PHT-based high-temperature piezoelectric ceramic material, characterized in that: The method for preparing the PYN-PHT-based high temperature piezoelectric ceramic material according to any one of claims 1 to 3 comprises the following steps: S1: According to the chemical formula 0.1Pb(Yb 0.5 Nb 0.5 )O3-0.9Pb(Hf 1-y Ti y )O3+xmol%(M'+M"), weigh a Nb-containing compound and a Yb-containing compound, mix them, and then perform ball milling, drying and sintering in sequence to obtain a precursor powder; S2: According to the chemical formula 0.1Pb(Yb 0.5 Nb 0.5 )O3-0.9Pb(Hf 1-y Ti y The precursor powder, the Pb-containing compound, the Ti-containing compound, the Hf-containing compound, the M'-containing compound, and the M"-containing compound are weighed and mixed to obtain a mixed powder; wherein M' represents an ionic radius of ions, M" represents the ionic radius ions, 0.1≤x≤2.0, 0.5≤y≤0.65; S3: ball milling, drying, sieving, pre-calcining and grinding the mixed powder in sequence to obtain a primary pre-calcined powder; S4: ball milling, drying, grinding and sieving the primary pre-burned powder in sequence to obtain a pre-synthesized powder; S5: pressing the pre-synthesized powder into sheets to obtain a ceramic green body; S6: The ceramic green body is sequentially subjected to vacuuming, isostatic pressing and sintering to obtain 0.1Pb(Yb 0.5 Nb 0.5 )O3-0.9Pb(Hf 1-y Ti y )O3+xmol%(M'+M")high temperature piezoelectric ceramic material.

5. The method for preparing a PYN-PHT-based high-temperature piezoelectric ceramic material according to claim 4, characterized in that: The Nb-containing compound includes Nb2O5; The Yb-containing compound includes Yb2O3.

6. The method for preparing a PYN-PHT-based high-temperature piezoelectric ceramic material according to claim 4, characterized in that: The Pb-containing compound includes Pb3O4; The Ti-containing compound includes TiO2; The Hf-containing compound includes HfO2; The M'-containing compound includes Li2CO3; The "M"-containing compound includes MoO3.

7. The method for preparing a PYN-PHT-based high-temperature piezoelectric ceramic material according to claim 4, characterized in that: In the step S1, ball milling includes: Anhydrous ethanol was used as a grinding agent and zirconium oxide balls were used as ball milling media for ball milling, wherein the ball milling time was 10 to 12 hours and the ball milling speed was 300 r / min; In the step S3 and the step S4, the ball milling includes: Anhydrous ethanol is used as a grinding agent, and a mixture of zirconia balls of a first particle size and a second particle size is used as a ball milling medium to ball mill the powder to be ball milled, wherein the ball milling time is 18 to 24 hours, the ratio of the powder to be ball milled to the grinding agent is 1g:1.5 to 2.0ml, and the ratio of the ball milling medium to the powder to be ball milled is 2.3 to 3:

1.

8. The method for preparing a PYN-PHT-based high-temperature piezoelectric ceramic material according to claim 4, characterized in that: In the step S1, the sintering temperature is 1050-1150° C., and the sintering time is 6 hours.

9. The method for preparing a PYN-PHT-based high-temperature piezoelectric ceramic material according to claim 4, characterized in that: In step S3, pre-burning includes: Put the powder to be pre-fired into a crucible and cover it, heat it to 600°C at a rate of 3°C / min, keep it warm for 60 minutes, then heat it to 850-950°C at a rate of 2.5°C / min, and keep it warm for 2-3 hours.

10. The method for preparing a PYN-PHT-based high-temperature piezoelectric ceramic material according to claim 4, characterized in that: In the step S6, sintering includes: In an atmospheric atmosphere, the temperature is raised to 800-900°C at a rate of 2.5°C / min, kept at this temperature for 30 minutes, and then raised to 1150-1250°C at a rate of 3°C / min, and fired at a constant temperature for 2-3 hours.

Citation Information

Patent Citations

  • Low temperature sintering lithium antimonite doped quinary system piezoelectric ceramics material and method for preparing same

    CN101337814A

  • Temperature-stable lead zirconate titanate-based high-temperature piezoelectric ceramic and preparation method thereof

    CN117534463A

  • Piezoelectric ceramic and laminated piezoelectric device

    CN1886352A

  • Improvements in or relating to piezoelectric ceramics

    GB1201159A